2019
DOI: 10.3390/ijms20184338
|View full text |Cite
|
Sign up to set email alerts
|

Function and Transcriptional Regulation of Bovine TORC2 Gene in Adipocytes: Roles of C/EBPγ, XBP1, INSM1 and ZNF263

Abstract: The TORC2 gene is a member of the transducer of the regulated cyclic adenosine monophosphate (cAMP) response element binding protein gene family, which plays a key role in metabolism and adipogenesis. In the present study, we confirmed the role of TORC2 in bovine preadipocyte proliferation through cell cycle staining flow cytometry, cell counting assay, 5-ethynyl-2′-deoxyuridine staining (EdU), and mRNA and protein expression analysis of proliferation-related marker genes. In addition, Oil red O staining analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…In silico analysis revealed that SNP3 neither gained nor loss of any new transcription factor binding site in the DNA sequence; however, this locus already contained binding sites for the MZF1, KLF1 and ZNF263 transcription factors, which remained intact as no loss occurred at this position. Moreover, previously, we confirmed the role of ZNF263 transcription factor in the regulation of TORC2 gene as transcriptional activator [10] Furthermore, SNP3 is located in the proximal minimal promoter region; therefore, these transcription factors may have a substantial role in the regulation of the TORC2 gene. In previous experiments conducted by our research group in the same breed of Qinchuan cattle, we demonstrated the role of the KLF transcription factor family and the MZF1 transcription factor in the regulation of genes responsible for adipogenesis and myogenesis [45,46].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In silico analysis revealed that SNP3 neither gained nor loss of any new transcription factor binding site in the DNA sequence; however, this locus already contained binding sites for the MZF1, KLF1 and ZNF263 transcription factors, which remained intact as no loss occurred at this position. Moreover, previously, we confirmed the role of ZNF263 transcription factor in the regulation of TORC2 gene as transcriptional activator [10] Furthermore, SNP3 is located in the proximal minimal promoter region; therefore, these transcription factors may have a substantial role in the regulation of the TORC2 gene. In previous experiments conducted by our research group in the same breed of Qinchuan cattle, we demonstrated the role of the KLF transcription factor family and the MZF1 transcription factor in the regulation of genes responsible for adipogenesis and myogenesis [45,46].…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, through the CREB pathway in coordination with peroxisome proliferator-activated receptor γ (PPARγ), coactivator 1α (PGC1α) and NR4A (nuclear receptor subfamily 4 group A), CRTC2 promotes gluconeogenesis, adipogenesis [7] and myogenesis [8]. In adipose tissue, TORC2 plays a role in the anabolic processes of adipocytes in lipid metabolism, including lipogenesis, adipogenesis and lipid esterification [9,10]. TORC2 is one of the main inhibitors of lipolysis by its regulation of PKA and HSL activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we explored several important transcription factors in the transcriptional regulation of the CRTC2 and CRTC1 genes (Khan, Raza, Junjvlieke, et al, 2019; Khan, Raza, Schreurs, et al, 2019). The transcription factors CEBP/G, XBP1, INSM1 , and ZNF263 were found to be the core regulatory elements responsible for transcription regulation of the CRTC2 gene, while NRF1 and SMAD3 were found to be the key regulators of the CRTC1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we targeted the transcription factors located in the promoter of CRTC1 and CRTC2 with bta-miR-149-5p. In our previous studies(Khan, Raza, Junjvlieke, et al, 2019;Khan, Raza, Schreurs, et al, 2019), these transcription factors including C/EBPγ, XBP1, INSM1, and ZNF263 regulated the CRTC2 gene, while NRF1 and SMAD3 regulated the CRTC1 gene. Obviously, most of the genes are synergistically regulated through a network of transcription factors and miRNAs.…”
mentioning
confidence: 77%
See 1 more Smart Citation